Avaliaçao na Educaçao Física Escolar : a produçao audiovisual como ferramenta pedagógica para a aprendizagem - Frizzo, Giovanni (Educación Física y Ciencia.)
This article is the result of a study that aimed to analyze the audiovisual production as an instrument of pedagogical evaluation in the Physical Education (PE) classes of the final years of Elementary School. We performed an action-research in a school of the municipal public system of the city of Pelotas-RS in the discipline of PE in a class of the final years of the Elementary School. The research took place during a semester and the audiovisual production was used as the instrument of evaluation. The results showed that the experience of producing videos as a facilitator tool in the construction of knowledge is pedagogically efficient and, at the same time, it receives the student's recognition and approval, which presupposes that the insertion of ICT in education and the application of this new evaluative format contribute to the improvement of the teaching-learning process